2010
DOI: 10.2174/1877611601002010051
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Scale Lateral Milling with Focused Ion Beam for Ultra-Smooth Optical Device Surface~!2009-12-16~!2010-02-18~!2010-04-21~!

Abstract: The effect of the nano-scale lateral milling process using a focused ion beam (FIB) was studied in order to prepare a flat and smooth surface suitable for the growth of optical device structures such as a distributed Bragg reflector (DBR) mirror on a rough gallium nitride (GaN) surface. A high-quality, smooth, and flat surface is very essential for high precision space optics. It was fabricated using the nano-scale lateral milling process and was analyzed using an atomic force microscope. A regular geometric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Argon ion milling was required before the sample underwent SEM analysis. The change of physical and chemical properties on the surface of samples can be eliminated by controlling the voltage and temperature during the argon ion-milling process. For example, Sanei et al suggested that initial heating caused by ion bombardment results in significant thermal alteration of the OM surfaces . Park et al has suggested a simple engineering model for the formation of regular geometric ripples made by the serial cutting sequence of a focused ion beam .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Argon ion milling was required before the sample underwent SEM analysis. The change of physical and chemical properties on the surface of samples can be eliminated by controlling the voltage and temperature during the argon ion-milling process. For example, Sanei et al suggested that initial heating caused by ion bombardment results in significant thermal alteration of the OM surfaces . Park et al has suggested a simple engineering model for the formation of regular geometric ripples made by the serial cutting sequence of a focused ion beam .…”
Section: Resultsmentioning
confidence: 99%
“…The change of physical and chemical properties on the surface of samples can be eliminated by controlling the voltage and temperature during the argon ion-milling process. For example, Sanei et al suggested that initial heating caused by ion bombardment results in significant thermal alteration of the OM surfaces . Park et al has suggested a simple engineering model for the formation of regular geometric ripples made by the serial cutting sequence of a focused ion beam . Bassim et al have shown that beam-induced heating was not observed to play a critical role in the potential alteration of functional chemistry by controlling the parameters such as final milling voltage, temperature, and ion beam overlap .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these mechanisms, the gallium ion (Ga + ) FIB has been shown to alter the thermal maturity of organic matter and the chemical structure of pyrite (Sanei & Ardakani, ). Moreover, other studies have shown Ga + FIB to heat samples to temperatures up to 1,000°C (Park et al, ). Based on these findings, we believe that the salt was destroyed by the FIB during three‐dimensional imaging before it could be observed.…”
Section: Resultsmentioning
confidence: 98%
“…The surfaces between movable beam and electrodes are assumed to be smooth. It has been reported that the smooth surfaces of the beam and the electrodes can be implemented using the focused ion beam (FIB) process with low beam current [12].…”
mentioning
confidence: 99%